First-Motion Focal Mechanism Solutions for 2015–2019 M ≥ 4.0 Italian Earthquakes - Ciaccio, Maria G.; Di Stefano, Raffaele; Improta, Luigi; Mariucci, Maria T.; , BSI Working Group; Castello, Barbara; Latorre, Diana; Margheriti, Lucia; Baccheschi, Paola; Lisi, Arianna; Marchetti, Alessandro; Nardi, Anna; et al. (Frontiers in Earth Science, 2021)
A list of 100 focal mechanism solutions occurred in Italy between 2015 and 2019 has been compiled for earthquakes with magnitude M≥4.0. We define earthquake parameters for additional 22 seismic events with 3.0≤M<4.0 for two specific key zones: Muccia, at the northern termination of the Amatrice-Visso-Norcia 2016-2018 central Italy seismic sequence, and Montecilfone (southern Italy) struck in 2018 by a deep, strike slip Mw5.1 earthquake apparently anomalous for the southern Apennines extensional belt. First motion focal mechanism solutions are a good proxy for the initial rupture and they provide important additional information on the source mechanism. The catalog compiled in the present paper provides earthquake parameters for individual events of interest to contribute, as a valuable source of information, for further studies as seismotectonic investigations and stress distribution maps. We calculated the focal mechanisms using as a reference the phase pickings reported in the Italian Seismic Bulletin (BSI). We visually checked the reference picks to accurately revise manual first-motion polarities, or include new onsets when they are not present in the BSI dataset, for the selected earthquakes within the whole Italian region, with a separate focus on the Amatrice-Visso-Norcia seismic sequence area from August 24th 2016 to August 24th 2018. For the Montecilfone area, we combined the information on the geometry and kinematics of the source of the 2018 Mw5.1 event obtained in this study with available subsurface and structural data on the Outer Apulia Carbonate Platform to improve understanding of this intriguing strike-slip sequence. Our analysis suggests that the Montecilfone earthquake ruptured a W-E trending strike-slip dextral fault. This structure is confined within the Apulia crystalline crust and it might represent the western prolongation of the Mattinata Fault - Apricena Fault active and seismogenic structures. The calculated focal mechanisms of the entire catalog are of good quality complementing important details on source mechanics from moment tensors and confirming the relevance of systematically including manually revised and more accurate polarity data within the BSI database.